Relationship between brain lesion characteristics and communication in preschool children with cerebral palsy - Coleman, A.; Fiori, S.; Weir, K.; Ware, R.; Boyd, Roslyn (Pergamon Press, 2016)
© 2016Background MRI shows promise as a prognostic tool for clinical findings such as gross motor function in children with cerebral palsy(CP), however the relationship with communication skills requires exploration. Aims To examine the relationship between the type and severity of brain lesion on MRI and communication skills in children with CP. Methods and procedures 131 children with CP (73 males(56%)), mean corrected age(SD) 28(5) months, Gross Motor Functional Classification System distribution: I = 57(44%), II = 14(11%), III = 19(14%), IV = 17(13%), V = 24(18%). Children were assessed on the Communication and Symbolic Behavioral Scales Developmental Profile (CSBS-DP) Infant-Toddler Checklist. Structural MRI was analysed with reference to type and semi-quantitative assessment of the severity of brain lesion. Children were classified for motor type, distribution and GMFCS. The relationships between type/severity of brain lesion and communication ability were analysed using multivariable tobit regression. Outcomes and results Children with periventricular white matter lesions had better speech than children with cortical/deep grey matter lesions (ß = -2.6, 95%CI = -5.0, -0.2, p = 0.04). Brain lesion severity on the semi-quantitative scale was related to overall communication skills (ß = -0.9, 95%CI = -1.4, -0.5, p < 0.001). Motor impairment better accounted for impairment in overall communication skills than brain lesion severity. Implications Structural MRI has potential prognostic value for communication impairment in children with CP. What this paper adds? This is the first paper to explore important aspects of communication in relation to the type and severity of brain lesion on MRI in a representative cohort of preschool-aged children with CP. We found a relationship between the type of brain lesion and communication skills, children who had cortical and deep grey matter lesions had overall communication skills > 1 SD below children with periventricular white matter lesions. Children with more severe brain lesions on MRI had poorer overall communication skills. Children with CP born at term had poorer communication than those born prematurely and were more likely to have cortical and deep grey matter lesions. Gross motor function better accounted for overall communication skills than the type of brain lesion or brain lesion severity.